Perforated peptic ulcer in children: diagnosis and treatment - Baltrūnaitė, Jūratė; Trainavičius, Kęstutis (Lietuvos chirurgija, 2015)
Objectives Perforated peptic ulcer (PPU) is a rare but life-threatening surgical emergency in childhood. The aim of our study was to analyse the clinical features, diagnosis and management of PPU in children. Methods The data of children diagnosed with gastroduodenal PPU at Children’s Surgery Department, Children’s Hospital, Affiliate of Vilnius University Hospital Santariskiu Klinikos from 1994 to 2012 were reviewed. The patients’ age, sex, anamnesis, clinical features, examination results, operative findings and methods, medication therapy and outcomes were assessed. Statistical analysis was performed using MS Excel. Results There were 14 (93.3%) males and one female aged 14 to 18 years (16.3 ± 1.3) included in the study. Twelve patients (80%) were diagnosed with gastric and 3 (20%) with duodenal PPU. Eleven patients (73.3%) had dyspepsia before PPU, of them 4 had a history of peptic ulcer disease. Most patients (46.6%) arrived to the hospital within 6 hours of symptom onset. All presented with severe epigastric pain, 8 (53.3%) with nausea and vomiting. Only one patient (6.6%) complained of melena. One (6.6%) suffered from epigastric pain radiating to the left shoulder. Physical examination revealed positive peritoneal signs in 13 patients (86.6%). Subdiaphragmatic free air was detected in 12 patients (80%). The mean duration of perforation was 34.47 ± 57.41 hours (2–178). Thirteen patients (86.6%) underwent laparotomy, 2 laparoscopic repair. The anterior wall of the prepyloric gastric region was the commonest perforation site (80%). Eight patients (53.4%) had a course of H. pylori eradication therapy. The average hospital stay was 10.6 ± 6.3 days (4–32). Fourteen patients (93.3%) had an uneventful postoperative period, one developed nephrotic range proteinuria. All recovered fully. Conclusions Gastroduodenal PPU should be suspected in adolescent boys with a sudden onset of severe abdominal pain, positive peritoneal signs, and confirmed by pneumoperitoneum in the plain X-ray. Simple closure and eradication of H. pylori (when infection confirmed) are mandatory for a complete recovery.